The effects of different follow-up management on asthma control: a prospective cohort study - Zhi Lu; Hongzhong Yang; Muyun Yan; Jun Liu; Lu Yang; Caixia Zhang; Da Liu (BMC Pulmonary Medicine)
Abstract Background Asthma is a chronic inflammatory disease of the airways. Proper use of inhaled medications and long-term standardized management are crucial for controlling asthma. In China, the morbidity of asthma among adults aged 20 and above is 4.2%, of which only 28.5% has been controlled. Objective This study aims to find the best model for long-term standardized asthma management by analyzing the effects of three follow-up methods: respiratory outpatient clinics follow-up, telephone follow-up, and WeChat follow-up on overall asthma control and patient medication compliance. Methods According to different follow-up methods, asthma patients were divided into a WeChat follow-up group (N = 140), a telephone follow-up group (N = 140), and an respiratory outpatient clinics follow-up group (N = 140), the three groups of patients underwent 12 months follow-up management. Outcomes were measured at baseline and after 1, 6, and 12 months of the intervention. The results of the assessment included the Medication Adherence Report Scale for Asthma (MARS-A), the Asthma Quality of Life Questionnaire (AQLQ), the Asthma Control Test Questionnaire (ACT), the satisfaction scale, the Beck Depression Inventory-II (BDI-II), the Global evaluation of treatment effectiveness (GETE), hospitalization, and emergency visits. Results Repeated measures analysis of variance showed that there were group effects and time effects on total MARS-A, ACT, BDI-II, GETE, and AQLQ in three groups (P < 0.001). Comparing the scores at the different times among the three groups, the results showed that the MARS-A, ACT, and AQLQ scores of the WeChat follow-up group were higher than those of the telephone follow-up group and the respiratory outpatient clinic follow-up group at 6 and 12 months after follow-up. In comparison, the BDI-II and GETE scores were lower than those of the telephone follow-up group and the respiratory outpatient clinic follow-up group (P < 0.05). Conclusion Our results demonstrate that all three follow-up methods improved asthma control, alleviate depression, and improve patient medication compliance, satisfaction, treatment effectiveness, and quality of life. However, the effect of the WeChat follow-up group is better than telephone follow-up and respiratory outpatient follow-up groups. Clinical trial number Not applicable.